2022
DOI: 10.5802/crgeos.103
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of décollement thickness on the evolution of décollement folds: insights from discrete element models

Abstract: We explored the influence of a variety of geometric and mechanical factors in the evolution of décollement folds above a weak décollement level in a sedimentary sequence. Under an applied overburden pressure, we construct nine discrete element models (DE-models) to test the effects of mechanical stratigraphy, the thickness of the décollement layer, and the number of strong and weak layers within the sedimentary cover sequence. The effects of the aforementioned parameters on the structural style of fold belts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The role of multiple detachment horizons on the dynamics of thrust systems (i.e., its strength and thickness) and the evolution of fold-and-thrust belts such as the Zagros (e.g., Sepehr et al, 2006;Sherkati et al, 2006;Vergés et al, 2011;Farzipour Saein and Koyi, 2016;Ghanadian et al, 2017b;Derikvand et al, 2018;Heydarzadeh et al, 2020Heydarzadeh et al, , 2021Koyi and Mansurbeg, 2021), the Jura Mountains (e.g., Schori et al, 2015;Smeraglia et al, 2021), the Pyrenees (e.g., Koyi and Sans 2006), the Northern Apennines of Italy (e.g., Massoli et al, 2006;Tavarnelli et al, 2019), US and Canadian Rocky Mountains (e.g., Bally et al, 1966;Fitz-Díaz et al, 2011), the southern Appalachian thrust belt (e.g., Rich, 1934;Thomas, 2019), and the Mexican fold-and-thrust belt (e.g., Higuera-Díaz et al, 2005;Fitz-Díaz et al, 2011;Cruz et al, 2019) have shown that deformation may be decoupled between different stratigraphic levels. This is of importance because the geometry, kinematics and mechanics of fold-and-thrust belts are strongly influenced by the geometric parameters and mechanical behaviour of detachments (Ruh et al, 2012(Ruh et al, , 2013Feng et al, 2015;Eslamirezaei et al, 2022). Detachments and their interactions decouple deformation between the underlying and overlying sedimentary package and develop specific structural styles in both laterally and with depth (e.g., Kukowski et al, 2002;Smit et al, 2003;Konstantinovskaya and Malavieille, 2011;Borderie et al, 2018;Meng and Hodgetts, 2019a, b;Dal Zilio et al, 2020;Santolaria et al, 2022).…”
Section: Role Of Detachments In the Evolution Of Thrust Sequencesmentioning
confidence: 99%
“…The role of multiple detachment horizons on the dynamics of thrust systems (i.e., its strength and thickness) and the evolution of fold-and-thrust belts such as the Zagros (e.g., Sepehr et al, 2006;Sherkati et al, 2006;Vergés et al, 2011;Farzipour Saein and Koyi, 2016;Ghanadian et al, 2017b;Derikvand et al, 2018;Heydarzadeh et al, 2020Heydarzadeh et al, , 2021Koyi and Mansurbeg, 2021), the Jura Mountains (e.g., Schori et al, 2015;Smeraglia et al, 2021), the Pyrenees (e.g., Koyi and Sans 2006), the Northern Apennines of Italy (e.g., Massoli et al, 2006;Tavarnelli et al, 2019), US and Canadian Rocky Mountains (e.g., Bally et al, 1966;Fitz-Díaz et al, 2011), the southern Appalachian thrust belt (e.g., Rich, 1934;Thomas, 2019), and the Mexican fold-and-thrust belt (e.g., Higuera-Díaz et al, 2005;Fitz-Díaz et al, 2011;Cruz et al, 2019) have shown that deformation may be decoupled between different stratigraphic levels. This is of importance because the geometry, kinematics and mechanics of fold-and-thrust belts are strongly influenced by the geometric parameters and mechanical behaviour of detachments (Ruh et al, 2012(Ruh et al, , 2013Feng et al, 2015;Eslamirezaei et al, 2022). Detachments and their interactions decouple deformation between the underlying and overlying sedimentary package and develop specific structural styles in both laterally and with depth (e.g., Kukowski et al, 2002;Smit et al, 2003;Konstantinovskaya and Malavieille, 2011;Borderie et al, 2018;Meng and Hodgetts, 2019a, b;Dal Zilio et al, 2020;Santolaria et al, 2022).…”
Section: Role Of Detachments In the Evolution Of Thrust Sequencesmentioning
confidence: 99%
“…In continuum models, abrupt brittle deformation at near‐surfaces may cause numerical instabilities due to mesh distortion and the strength contrasts between air and sediment. The discrete element method (DEM), a particle‐based numerical approach, has been widely adopted for modeling multiscale (e.g., minerals to rocks) particle behaviors in geological structures such as fold‐and‐thrust belts (Eslamirezaei et al., 2022; Hardy & Cardozo, 2021), thrust‐related faults (Meng & Hodgetts, 2019, 2020), and normal faults (Botter et al., 2014; Smart & Ferrill, 2018). The DEM captures the brittle deformation of tectonic structures by simulating mechanical interactions between particles without mesh distortion‐related numerical instability.…”
Section: Introductionmentioning
confidence: 99%
“…These factors have been studied, such as the presence of pre-existing structures [e.g., Nilforoushan et al, 2013, Nabavi et al, 2020, Del Ventisette et al, 2021, Najafi et al, 2021, Shamszadeh et al, 2022a, basement morphology and thrust ramp dip angle [e.g., Maillot and Koyi, 2006, Rosas et al, 2017, Caër et al, 2018, Ghosh et al, 2020, the depositional environment, mechanical stratigraphy (i.e. the mechanical properties, thickness of layers, and interface properties of rock units) [e.g., Cruz et al, 2008, Farzipour-Saein and Koyi, 2014, Pla et al, 2019, Ito and Moore, 2021, the presence of décollements (single and/or multiple) and their initial configurations [e.g., Sherkati et al, 2006, Stockmal et al, 2007, Graveleau et al, 2012, Nilforoushan et al, 2012, Ruh et al, 2012, 2017, Watkins et al, 2014, Ghanadian et al, 2017a,b, Li and Mitra, 2017, Borderie et al, 2018, Derikvand et al, 2018, Heydarzadeh et al, 2020, Gu et al, 2021, Eslamirezaei et al, 2022, Mohammadrezaei et al, 2022, the basal slope and velocity [e.g., Rosas et al, 2017], the basal friction [e.g., Cotton and Koyi, 2000, Costa and Vendeville, 2002, Koyi and Maillot, 2007, the angle of convergence [e.g., Casas et al, 2001, Mc-Clay et al, 2004, Leever et al, 2011…”
Section: Introductionmentioning
confidence: 99%